Critical dependence of magnetostructural coupling and magnetocaloric effect on particle size in Mn-Fe-Ni-Ge compounds - Wu, Rongrong (Sci Rep, 2016)
Magnetostructural coupling, which is the coincidence of crystallographic and magnetic transition, has obtained intense attention for its abundant magnetoresponse effects and promising technological applications, such as solid-state refrigeration, magnetic actuators and sensors. The hexagonal Ni(2)In-type compounds have attracted much attraction due to the strong magnetostructural coupling and the resulted giant negative thermal expansion and magnetocaloric effect. However, the as-prepared samples are quite brittle and naturally collapse into powders. Here, we report the effect of particle size on the magnetostructural coupling and magnetocaloric effect in the Ni(2)In-type Mn-Fe-Ni-Ge compound, which undergoes a large lattice change across the transformation from paramagnetic austenite to ferromagnetic martensite. The disappearance of martensitic transformation in a large amount of austenitic phase with reducing particle size, to our best knowledge, has not been reported up to now. The ratio can be as high as 40.6% when the MnNi(0.8)Fe(0.2)Ge bulk was broken into particles in the size range of 5~15 μm. Meanwhile, the remained magnetostructural transition gets wider and the magnetic hysteresis becomes smaller. As a result, the entropy change drops, but the effective cooling power RC(effe) increases and attains to the maximum at particles in the range of 20~40 μm. These observations provide constructive information and highly benefit practical applications for this class of novel magnetoresponse materials.